NEGRAS, CABRAS E PARDAS NO BANCO DOS RÉUS NA VILA REAL DE NOSSA SENHORA DA CONCEIÇÃO DO SABARÁ E VILA DE NOSSA SENHORA DO CARMO (1770-1830) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
The central theme of this research is to analyze crime processes involving black women, Browns and goats in the captaincy of Minas Gerais in the 1770-1830 period. We analyze the conflicts and tensions that led some of these women, in the dockin the 18th century. Seeking to rebuild economic and social aspects in relationship with the crime committed by black women. The clipping space, we privilege the villages of Nossa senhora do Carmo and the Vila de Nossa Senhora da Conceição do Sabará. The processes crime chosen do part of the collections of the 18th century House of Mariana, Borba Gato in Sabará, Overseas File. This documentation, It consists of testimonies and ' testimonials depicting aspects of social relations of violence. The dissertation aims to rebuild from women's daily crimes processes mining, clashes and alliances established between these historical subjects, who had your daily life heavily marked by interpersonal violence and criminality.
Keywords: Pardas; Negras; Negras; Cabras; Processos crime; Minas Gerais; Browns; Black girls; Goats; Crime processes; Minas Gerais; CNPQ::CIENCIAS HUMANAS::HISTORIA